Bimbingan Teknis Legalitas Usaha dan Strategi Pemasaran Digital pada UMKM di Desa Sengon - Khamim Hariyadi; Deni Riani; Prisna Aura Rahma Putri; Windy Amelia Wahyuni; Alviona Nurul Huda; Meisy Eka Andriana; Septi Tiaradinar (Lembaga Pengembangan Kinerja Dosen, 2024)
Business legality is something that MSMEs must have. Business legality is a business identity and a form of protection provided by the government for perpetrators MSMEs. Another benefit of legal business ownership is to expand access to MSME financing provided by the government and access to financing from banks. Problems that occur is that many MSME players do not understand how important it is to have business legality the. Apart from that, there is an opinion that managing complicated business legalities is one of them the reason why MSMEs are reluctant to take care of their legality. This service activity has the aim of:educate regarding the urgency of business legality for MSMEs. This activity was carried out in Sengon Village, Bendungan subdistrict. The results of this activity can be seen from the enthusiasm of the participants in participating technical guidance activities on the legality of MSMEs and increasing their knowledge.